2021
DOI: 10.18632/aging.203711
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genomic structure variants associated with wrinkled skin in Xiang pig by next generation sequencing

Abstract: Wrinkling is prominent manifestation of aging skin. A mutant phenotype characterized by systemic wrinkles and thickened skin was discovered in Xiang pig populations with incidence about 1-3%. The feature in histological structure was epidermal hyperplasia and thickening, collagen fibers disorder. To uncover genetic mechanisms for the mutant phenotype of Xiang pigs with systemic wrinkle (WXP), a genome-wide of structural variations (SVs) in WXP was described by next generation resequencing, taking Xiang pigs (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Economic growth and increased longevity have given rise to the pursuit of beauty and the active search for new bioactive substances that can fight age and promote health 1 . Skin aging is mainly characterized by structural and functional changes put into the epidermis and dermis 2 . Collagen, a major component of the extracellular matrix (ECM), is synthesized by dermal fibroblasts to maintain the skin's strength and elasticity 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic growth and increased longevity have given rise to the pursuit of beauty and the active search for new bioactive substances that can fight age and promote health 1 . Skin aging is mainly characterized by structural and functional changes put into the epidermis and dermis 2 . Collagen, a major component of the extracellular matrix (ECM), is synthesized by dermal fibroblasts to maintain the skin's strength and elasticity 3 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Skin aging is mainly characterized by structural and functional changes put into the epidermis and dermis. 2 Collagen, a major component of the extracellular matrix (ECM), is synthesized by dermal fibroblasts to maintain the skin's strength and elasticity. 3 However, UV rays, skin inflammation, intracellular metabolites, and aging can inhibit collagen synthesis, leading to skin aging occurrences such as wrinkle formation, sagging, and laxity.…”
Section: Introductionmentioning
confidence: 99%
“…Our transcriptome analysis indicated that the genes, such as IRS2, FOXO1, and GLUT4, involved in the insulin signaling response were also more highly expressed in the longissimus dorsi muscle of Xiang pigs than in Large White pigs, which is consistent with previous studies that up regulated genes involved in insulin signaling pathway and insulin resistance in local pig breeds compared to western commercial pigs 14,34 . Interestingly, we observed that some genes harboring SV were enriched in the insulin signaling pathway 29 ) appeared more frequently in Xiang pigs than in Large White pigs, suggesting that variation in these genes may leads to high expression of related genes in the insulin signaling related pathway in Xiang pigs. In addition, the PFKFB3 gene regulates the synthesis and degradation of fructose-2, 6-bisphosphate and fructose-6-phosphate during glucose metabolism.…”
Section: Functional Analysis Of Degs Involved In Meat Quality Traitsmentioning
confidence: 84%
“…We further collected genetic variation between Xiang pigs and Western commercial pigs previously reported by our group 29 , and we found 75 DEGs covering 152 loci of structural variation (SV), which deletion accounted for the major type of variation and most of the variations were located in introns (Table S11, Fig. 5A,B).…”
Section: Functional Analysis Of Degs Involved In Meat Quality Traitsmentioning
confidence: 99%
“…These genes are involved in cell lamin filament, intermediate filament cytoskeletons, supramolecular complexes, cell differentiation, regulation of macromolecule metabolic processes, etc. [ 16 ]. However, the roles of FUT8 regulating E. coli F18 susceptibility in IPEC-J2 cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%